Deformation mechanism of bimodal microstructure in Ti-6Al-4V alloy: The effects of intercritical annealing temperature and constituent hardness. (30th April 2021) - Chong, Yan; Bhattacharjee, Tilak; Tian, Yanzhong; Shibata, Akinobu; Tsuji, Nobuhiro
Abstract: The so-called bimodal microstructure of Ti-6Al-4V alloy, composed of primary α grains ( α p ) and transformed β areas ( β trans ), can be regarded as a "dual-phase" structure to some extent, the mechanical properties of which are closely related to the sizes, volume fractions, distributions as well as nano-hardness of the two constituents. In this study, the volume fractions of primary α grains (vol.%( α p )) were systematically modified in three series of bimodal microstructures with fixed primary α grain sizes (0.8 μm, 2.4 μm and 5.0 μm), by changing the intercritical annealing temperature ( T int ). By evaluating the tensile properties at room temperature, it was found that with increasing T int (decreasing vol.%( α p )), the yield strength of bimodal microstructures monotonically increased, while the uniform elongation firstly increased with T int until 910 °C and then drastically decreased afterwards, thereby dividing the T int into two regions, namely region I (830−910 °C) and region II (910−970 °C). The detailed deformation behaviors within the two regions were studied and compared, from the perspectives of strain distribution analysis, slip system analysis as well as dislocation analysis. For bimodal microstructures in region I, due to the much lower nano-hardness of β trans than α p, there was a clear strain partitioning between the two constituents as well as a strain gradient from the α p / β trans interface to the grain interior of α p . This activated a large number of geometrically necessary dislocations (GNDs) near the interface, mostly with <c+a > components, which contributed greatly to the extraordinary work-hardening abilities of bimodal microstructures in region I. With increasing T int, the α p / β trans interface length density gradually increased and so was the density of GNDs with <c+a > components, which explained the continuous increase of uniform elongation with T int in this region. For bimodal microstructures in region II, where the nano-hardness of β trans and α p were comparable, neither a clear strain-partitioning tendency nor a strain gradient across the α p / β trans interface was observed. Consequently, only statistically stored dislocations (SSDs) with component were activated inside α p . The absence of <c+a > dislocations together with a decreased volume fraction of α p resulted into a dramatic loss of uniform elongation for bimodal microstructures in region II.